Basic chemistry. - Daub, G. William; Seese, William S. (Englewood Cliffs, N.J. Prentice Hall, 1992)
An introduction to the basic principles of chemistry that draws on the student's own experiences through analogies and cartoons to learn difficult concepts. This book is useful to courses in Introduction to Chemistry and Preparatory Chemistry (in preparation for two-term general chemistry).
includes index.
Keywords: Chemistry